DEPOSITIONAL PROCESSES AND FACIES ARCHITECTURE OF BALIKPAPAN SANDSTONE FORMATION, APPLICATION OF 3D DIGITAL OUTCORP MODEL (DOM) TO IDENTIFY RESERVOIR GEOMETRY AND DISTRIBUTION IN DELTAIC SYSTEM - Rian Cahya Rohmana; Iqbal Fardiansyah; Leon Taufani; Dicky Harishidayat (Testing Center for Oil and Gas LEMIGAS, 2019)
In recent years, digitalization of the outcrop technique is a powerful tool - for detailed analysis on the geo-software. Thus, the integration between outcrops and subsurface data for reducing the subsurface uncertainties. This provides the impetus to propose and accomplish a holistic understanding of the architecture and geometry of the deltaic system and to provide an exhaustive analysis of their sedimentary processes. This study investigates the temporal and spatial distribution of deltaic sandstone using a combination of 3D Digital Outcrop Model (DOM) application and traditional geologic mapping of Balikpapan Formation in the Kutei Basin. Our study has successfully revealed that DOM is an excellent method to better understand the depositional process and facies architecture within the heterogeneity of deltaic system. The classification scheme presented in this study is also applicable to other sedimentological settings worldwide.